CHANGE OF ORAL LIQUID PROPERTIES UNDER TREATMENTS DEVELOPED INFLAMMATION OF PERIODONTAL TISSUES IN PATIENTS CONSTRUCTIONS WITH FIXED DENTURE IN MOUTH CAVITY DYNAMICS - O. Petrushanko; S. Hermanchuk (Український стоматологічний альманах)
Abstract. In the article the author presents change of oral fluid properties under the influence of treatments developed inflammation of periodontal tissue in patients with fixed constructions of dentures in the mouth dynamics.